South Africa Digital Economy Assessment - World Bank (World Bank, Washington, DC, 2020)
An assessment of South Africa’s digital economy has been launched as part of the World Bank Group’s digital economy for Africa (DE4A) initiative, which leverages an integrated and foundations-based diagnostic framework to examine the present level of digital economy development across Africa. The assessment will map the current strengths and weaknesses that characterize the national digital economy ecosystem, as well as identify challenges and opportunities for future growth. Rapid digital transformation is now re-shaping the global economy, permeating virtually every sector and aspect of daily life - changing the way one learns, work, trade, socialize, access public and private services and information. Well-functioning digital economies are thus expected to achieve faster economic growth, offer innovative products and services, as well as create more job opportunities. Assessing where strategic investments and interventions need to be made is a critical first step to enabling digital economy growth. This background paper will provide an overview of digital entrepreneurship in South Africa.